Geo-pedological contribution to the reconstruction of Holocene activity of Chaitén volcano (Patagonia, Chile). (October 2019) - Casati, Enrico; D'Amico, Michele; Šefrna, Ludek; Trombino, Luca; Tunesi, Annalisa; Previtali, Franco
Abstract: On May 2, 2008, the Chaitén volcano, located in Chilean Patagonia, thought to be inactive for almost 10, 000 years, erupted, emitting pyroclastic materials (ash and pumice) of rhyolitic composition. The ejected materials partially burned the forest vegetation in a wide radius, blocked the river systems, causing local flooding, and forced the majority of the inhabitants to abandon the nearby village of Chaitén. In 2005, 2009, the authors surveyed and sampled a number of paleosols and tephra sections located just north of the village. The present work shows the results of pedological, micromorphological, petrographic, and geochemical analyses, accompanied by radiocarbon dating, The studies have shown the presence of different soil complexes (Andosols), developed from pyroclastic materials and separated by erosional surfaces. Under the modern soil, consisting only of A horizons, paleosols follow with pedogenized horizons overlying altered and hardened volcanic materials. The mineralogical and geochemical analyses confirmed the sequence of these complexes and distinguished a double origin of the materials from which they developed: the most recent and superficial soil, although not significantly affected by the depositions of the last eruption, presented an evident geochemical and mineralogical affinity with tephra of the Chaitén volcano, differently from those of the deeper paleosols which have been found to derive from the ejecta of Michinmahuida volcano. The evolutionary model of the soils of the area has also been confirmed by the dates measured along the studied sections that are comparable with the dates of volcanic events during the Holocene already ascertained by the most recent volcanological studies. Highlights: Modern soils, paleosols and tephra have been studied in a volcanic area in Chilean Patagonia. Pedological and geochemical approach allowed to set soils evolution and to recognize the genesis from two eruptive centers. Dates of soils match well with the chronology of volcanic events recognized by recent geological studies in the area.